The Effect of Different Stocking Densities on Growth and Survival Rate of Giant Prawns (Macrobrachium rosenbergii) in the Biofilter Recirculation System - Tobing, Olaelita L; Rusliadi, Rusliadi; Masjudi, Heri (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2025)
This research aims to determine the effect of different stocking densities on the growth and survival of Giant prawns (Macrobrachium rosenbergii) which are reared using a biofilter recirculation system. This research was conducted from June to July 2024 at the Cultivation Technology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This research used a one-factor Completely Randomized Design (CRD) method with four treatment measures and three replications. The treatment levels applied in this study were stocking density 20 fish/m2, stocking density 40 fish /m2, stocking density 60 fish /m2, and stocking density 80 fish /m2. The results of the study showed that different stocking densities had a significant effect (P<0.05) on the growth performance of Giant prawns. The best treatment was found at a stocking density of 80 fish /m2 which resulted in growth in absolute weight 2.34 g, absolute length 3.96 cm, specific growth rate 2.59%, survival rate was 98.33% and THC value was 20.654×106 cells/mL.